2022
DOI: 10.1039/d2cc02261c
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic nitrate reduction to ammonia via amorphous cobalt boride

Abstract: Electrocatalytic nitrate reduction reaction (NitRR) is an energy-saving and environmentally benign approach to synthesizing ammonia under ambient conditions. However, the development of noble metal-free catalysts with high activity and selectivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…5d and N 2 activation by stabilizing intermediate species through charge modulation. 18,19,84 Thus, TiB 2 can act as an excellent catalyst for nitrogen reduction reaction. In addition, TiB 2 nanosheets after N 2 adsorption can potentially be used as an excellent H 2 storage material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5d and N 2 activation by stabilizing intermediate species through charge modulation. 18,19,84 Thus, TiB 2 can act as an excellent catalyst for nitrogen reduction reaction. In addition, TiB 2 nanosheets after N 2 adsorption can potentially be used as an excellent H 2 storage material.…”
Section: Resultsmentioning
confidence: 99%
“…For example, MgB 2a flagship member of this familyis known for its superconductivity; 16 TiB 2 is used in ballistic armors; 17 and recently, CoB 2 and MoB 2 have found application in the hydrogen evolution reaction (HER) and nitrogen reduction reaction (NRR). 18,19 The perspective on using metal diborides in their native bulk form has been fast evolving since 2015, when our group reported that it is possible to delaminate MgB 2 into nanosheets using ultrasonication; it was the first report that showcased such feasibility. 20 Since then, several approaches for nanoscaling MgB 2 have been reported: chelation, 21,22 dissolution-recrystallization, 23 cation exchange, 24 interlayer expansion, 25 ultrasonication in ionic liquids/organic solvents, 26,27 and ball-milling.…”
Section: Introductionmentioning
confidence: 99%
“…36 Therefore, amorphous engineering is considered to be an effective method to adjust catalyst structure and improve electrocatalytic performance. Recently, some amorphous catalysts have been reported in nitrate reduction to ammonia processes, such as amorphous RuO 2 nanosheets, 37 amorphous cobalt boride, 38 amorphous FeB 2 porous nanosheets 39 and so on, all of which exhibited high electrocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…30 The close-packed FeN 4 catalytic centers perform NO 2 À binding and multielectron reduction and well-oriented peripheral amino acid channels assist proton shuttling and N-H bond formation. [30][31][32][33] Since cobalt demonstrates the optimum NO 2 À binding and N-O bond dissociation thermodynamics in the catalytic volcano plot, 34,35 Co-based heterogeneous nanomaterials, including metallic Co, 36 oxides, 37,38 borides 39 and phosphides 40 with diverse structures and morphologies, attain attractive eNO x À RR current densities, but the unclear atomic active sites and uncontrollable secondsphere structures hamper rational catalyst development and optimization. On the other hand, eNO x À RR can be catalysed by homogeneous, macrocyclic Co complexes, [41][42][43][44][45][46] but realizing complete and high-yield NO 2 À to NH 4 + transformation is particularly challenging under mild potentials, due to the inefficiency of consecutive 6e À transfer to the catalytic centre.…”
mentioning
confidence: 99%